2019
DOI: 10.1186/s12870-018-1600-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SrDXS1 and SrKAH enhances steviol glycosides content in transgenic Stevia plants

Abstract: BackgroundStevia rebaudiana produces sweet-tasting steviol glycosides (SGs) in its leaves which can be used as natural sweeteners. Metabolic engineering of Stevia would offer an alternative approach to conventional breeding for enhanced production of SGs. However, an effective protocol for Stevia transformation is lacking.ResultsHere, we present an efficient and reproducible method for Agrobacterium-mediated transformation of Stevia. In our attempts to produce transgenic Stevia plants, we found that prolonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
244
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 448 publications
(259 citation statements)
references
References 43 publications
15
244
0
Order By: Relevance
“…After confirmation by sequencing, the expression vector was transformed into the Agrobacterium strain AGL2. Transformation of Stevia using this Agrobacterium was well described (Zheng et al, 2018). Briefly, the leaf explants were co-cultivated with Agrobacterium on co-cultivation media (0.25 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) + 100 lM acetosyringone) for 3 days and transferred onto callus induction media (1 mg/L 6-benzylaminopurine (BA) + 0.5 mg/L 3-indoleacetic acid (IAA) + 125 mg/L cefotaxime + 50 mg/L kanamycin) after washing.…”
Section: Stevia Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…After confirmation by sequencing, the expression vector was transformed into the Agrobacterium strain AGL2. Transformation of Stevia using this Agrobacterium was well described (Zheng et al, 2018). Briefly, the leaf explants were co-cultivated with Agrobacterium on co-cultivation media (0.25 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) + 100 lM acetosyringone) for 3 days and transferred onto callus induction media (1 mg/L 6-benzylaminopurine (BA) + 0.5 mg/L 3-indoleacetic acid (IAA) + 125 mg/L cefotaxime + 50 mg/L kanamycin) after washing.…”
Section: Stevia Transformationmentioning
confidence: 99%
“…gDNAs extracted from the SrUGT76G1-OE lines were digested with HindIII and resolved on a 0.8% agarose gel together with the DIG-labelled DNA molecular weight marker II (Roche, Mannheim, Germany). The agarose gel was then treated for the transfer of fragmented gDNAs onto a positively charged nylon membrane (Hybond-N+) as mentioned previously (Zheng et al, 2018). Following DIG-based Southern blot hybridization (Roche), chemiluminescence from the membrane was detected using the ChemiDoc Touch Imaging System (Bio-Rad, Hercules, CA).…”
Section: Verification Of Transgenic Stevia Plants By Genomic Pcr Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent induction of callus and the maintenance of callus under Hyg selection was also conducted in the dark until regeneration. Very recently, researchers reported using tissue cultured leaves as the explant and successfully obtained stable transgenic Stevia plants 9,26 ; this suggests that both types of originating explant are suitable for efficient transformation. Similar to our results, this same research group also concluded that a prolonged period of dark incubation was critical for obtaining high efficiency Stevia transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, successful recovery of transgenic Stevia callus, but not whole plants, was documented using a GUS-bar construct delivered via particle bombardment 25 . Very recently, a research group from the University of Singapore described the stable transformation of Stevia using kanamycin as the selectable marker and GFP as a reporter gene 9,26 .…”
mentioning
confidence: 99%